Stimulated release of arachidonate and prostaglandins is vectorial in MDCK epithelial cells - Cortizo, Ana María (1992)
The receptor mediated activation of phospholipase A2by appropriate ligands results in the synthesis and release of eicosanoids, a class of potent bioregulatory molecules. Madin-Darby canine kidney cells (MDCK) are polarized epithelial cells, with structurally and functionally distinct plasma membrane domains separated by tight junctions. Using MDCK cells grown in dual sided chambers, we show in this report, that a) the receptor mediated release of prostaglandins and arachidonate into the extracellular medium is predominantly unidirectional, b) the direction of release is agonist specific, and c) the magnitude of the response due to a given agonist is cell-domain specific. These characteristics, if operativein vivo, would contribute towards the optimal function of trans-cellular metabolism of eicosanoids already demonstrated.